Late Latent Syphilis in Pregnancy: A Case Report - Dewi, Molla Andriska; Nadeak, Kristina (Jurnal Ners, 2025)
Introduction Syphilis is a chronic sexually transmitted infection caused by Treponema pallidum, with latent stages posing particular risks in pregnancy due to vertical transmission and adverse fetal outcomes. Although treatable with penicillin, late latent syphilis often remains undiagnosed until routine antenatal screening. Case Presentation A 19-year-old woman, G2P1A0, at 21 weeks’ gestation, presented with a positive Venereal Disease Research Laboratory (VDRL) test during antenatal care. She denied history of genital ulcers, systemic symptoms, or multiple partners, but her husband had a history of untreated genital lesions and was seropositive for syphilis. Examination showed no mucocutaneous or systemic abnormalities. Laboratory evaluation confirmed late latent syphilis (VDRL 1:64; TPHA 1:5,120). The patient was treated with intramuscular benzathine penicillin G, 2.4 million units weekly for three weeks. Serial follow-up showed a progressive decline in VDRL titers (1:64 → 1:32 → 1:16 over six months). Pregnancy continued uneventfully. Conclusion Early detection and treatment of late latent syphilis in pregnancy are critical to prevent vertical transmission and adverse perinatal outcomes. Routine antenatal screening remains a cornerstone of maternal and child health programs.